2021
DOI: 10.1097/md.0000000000024541
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of immunosuppressive therapies in the treatment of high-risk IgA nephropathy

Abstract: Background: IgA nephropathy (IgAN) is one of the significant contributing factors of end-stage renal disease (ESRD). It is reported that over half of patients with IgAN accompany multiple high-risk factors, which increase the risk of ESRD progression. Studies have shown that immunosuppressive agents were beneficial in high-risk IgAN, but the efficacy and safety have not been fully demonstrated yet. The present study aims to elucidate the efficacy of commonly used immunosuppressants in high-risk IgA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Moreover, the inclusion criteria for the meta-analysis are not restricted, and studies with various treatment regimens in control groups were included, such as those with CS alone, ACEI/ARB alone, placebo or blank treatment, or the other immunosuppressants, which made the interpretation of the result difficult. Recently, a well-designed network meta-analysis was performed to evaluate the efficacy and safety of different immunosuppressants for high-risk IgAN [ 41 ]. Although this study could provide more information and consistently showed that combined leflunomide with CS could serve as one of the best choices for patients with high-risk IgAN [ 41 ], results of network meta-analysis were generally based on studies of indirect comparison, which may limit the reliability of the findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the inclusion criteria for the meta-analysis are not restricted, and studies with various treatment regimens in control groups were included, such as those with CS alone, ACEI/ARB alone, placebo or blank treatment, or the other immunosuppressants, which made the interpretation of the result difficult. Recently, a well-designed network meta-analysis was performed to evaluate the efficacy and safety of different immunosuppressants for high-risk IgAN [ 41 ]. Although this study could provide more information and consistently showed that combined leflunomide with CS could serve as one of the best choices for patients with high-risk IgAN [ 41 ], results of network meta-analysis were generally based on studies of indirect comparison, which may limit the reliability of the findings.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a well-designed network meta-analysis was performed to evaluate the efficacy and safety of different immunosuppressants for high-risk IgAN [ 41 ]. Although this study could provide more information and consistently showed that combined leflunomide with CS could serve as one of the best choices for patients with high-risk IgAN [ 41 ], results of network meta-analysis were generally based on studies of indirect comparison, which may limit the reliability of the findings. For the comparison of LEF + CS vs CS, RCTs are adequate for a meta-analysis of head-to-head comparison, like ours.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, immunosuppressants are emerging as a new class of drugs that exhibit anti-tumor effects [1][2][3] . Compared to traditional chemotherapy drugs, such as cis-platin and others which possess strong cytotoxicity [4][5] , immunosuppressants have significantly reduced toxicity [6][7] . FTY720 is a clinically approved immunosuppressant 8 and has recently been shown to exert efficient antitumor activity 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Representative candidates include rapalogs such as rapamycin and everolimus [1,3], fingolimod (FTY720) [4], prodigiosins (PrGs) [5], capecitabine [6], and others. Compared to traditional chemotherapy drugs, such as cis-platin and others, which possess strong cytotoxicity [7,8], immunosuppressants have significantly reduced toxicity [9,10]. FTY720 is a clinically approved immunosuppressant [11] and has recently been shown to exert efficient antitumor activity [4].…”
Section: Introductionmentioning
confidence: 99%